Obsessive-compulsive tendencies are associated with a focused information processing strategy. - Soref, Assaf; Dar, Reuven; Argov, Galit; Meiran, Nachshon (Behaviour Research & Therapy, 2008)
The study examined the hypothesis that obsessive-compulsive (OC) tendencies are related to a reliance on focused and serial rather than a parallel, speed-oriented information processing style. Ten students with high OC tendencies and 10 students with low OC tendencies performed the flanker task, in which they were required to quickly classify a briefly presented target letter (S or H) that was flanked by compatible (e.g., SSSSS) or incompatible (e.g., HHSHH) noise letters. Participants received 4 blocks of 100 trials each, two with 50% compatible trials and two with 80% compatible trials and were informed of the probability of compatible trials before the beginning of each block. As predicted, high OC participants, as compared to low OC participants, had slower overall reaction time (RT) and lower tendency for parallel processing (defined as incompatible trials RT minus compatible trials RT). Low, more than high OC participants tended to adjust their focused/parallel processing including a shift towards parallel processing in blocks with 80% compatible trials and in trials following compatible trials. Implications of these results to the cognitive theory and therapy of OCD are discussed. Copyright (c) 2008 Elsevier Ltd.